2018
DOI: 10.1002/pon.4920
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive dysfunction in adult cerebellar medulloblastoma

Abstract: Objective Impaired neurocognitive function (NCF) is a well‐established consequence of pediatric medulloblastoma (MB) and its treatments. However, the frequency and features of neurocognitive dysfunction in adult‐onset MB patients are largely unknown. Methods Adult patients (≥ 18 years) with MB who had received formal neurocognitive evaluation (N = 27) were identified. Demographic, medical, and treatment histories were extracted from the medical record. Lesion properties on MRI were analyzed and used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Historically, these patients have been treated with high-or low-dose RT and first-line chemotherapy to minimize the risk of cognitive side effects of high-dose RT. 34 , 35 In this study, we determined the effect of RT dose on outcome in standard-risk patients; we did not detect a difference in patients who received < 30 Gy RT plus adjuvant chemotherapy and those who received ≥ 30 Gy RT alone.…”
Section: Discussionmentioning
confidence: 96%
“…Historically, these patients have been treated with high-or low-dose RT and first-line chemotherapy to minimize the risk of cognitive side effects of high-dose RT. 34 , 35 In this study, we determined the effect of RT dose on outcome in standard-risk patients; we did not detect a difference in patients who received < 30 Gy RT plus adjuvant chemotherapy and those who received ≥ 30 Gy RT alone.…”
Section: Discussionmentioning
confidence: 96%
“…The impact of treatment on neurocognition and HRQoL in adult medulloblastoma patients is understudied. A recent study reported impaired neurocognitive functioning (learning and memory, and executive function) shortly after diagnosis [13], while another study reported that adult medulloblastoma patients had problems with executive dysfunction, weakness, ataxia, depression or anxiety about nine years after radiotherapy [14]. These long-term sequelae may subsequently have a negative impact on HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most relevant long-term complications of radiotherapy in brain tumor patients is neurocognitive dysfunction [12], which may subsequently interfere with a patients' functioning in daily life, particularly role and social functioning. Although it has been shown that a large proportion of adult medulloblastoma patients have impaired neurocognitive functioning shortly after diagnosis, particularly in the domains learning, memory, and executive function [13], data on the short-and long-term impact of treatment on outcomes such as neurocognition and HRQoL are limited. One study reported impaired executive function, weakness, ataxia, depression and anxiety about nine years after radiotherapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies of adult MB survivors have been conducted. Harrison et al, conducted a cross-sectional study of 27 patients treated for MB during early adulthood in which 25–30% of patients displayed impaired executive function and new-learning performance that correlated with the amount of chemotherapy cycles received [ 39 ]. Dirven et al reported on 28 patients treated with radiation and chemotherapy.…”
Section: Translational Researchmentioning
confidence: 99%